The The Role Of Digital Leadership And Digital Self-Efficacy On Subjective Career Success In The Startup Company - Tika Siregar (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Digital transformation has introduced new technologies, reshaping how companies operate and creating new career opportunities and challenges. The objective of this study is to examine the influence of digital leadership an digital self-efficacy on the subjective career success of startup employee. This study included a sample of 200 workers from startup company in West Sumatera. Using the Partial Least Squares software, this study applies Structural Equation Modelling analysis to examine the hypotheses. The findings of the research indicate that digital leadership and digital self-efficacy exert a positive and significant influence on subjective career success. The study extends the career success literature by emphasizing the growing relevance of digital competencies and leadership in contemporary careers, and it offers valuable insights for organizations seeking to enhance employees’ career outcomes in the digital era.